Why a national strategy for exploiting information technologies. - HANNA, Nagy (1995)
Identifies three perspectives from which the need for a national information technology (IT) strategy may be viewed, viz: IT is a strategic industry; IT is a key generic technology, whose applications span all industries and services; and, IT is an essential infrastructure that allows the sharing of knowledge, and the collection, processing and transmission of information at breathtaking speed and at declining cost, thereby increasing productivity and improving quality and efficiency in all types of industries and services. Contends that national strategies for IT need to be timed and tailored to the level of economic and industrial development.